P745 Incidence of indeterminate colitis in the EPIMAD registry decreases over the period 1988–2014. (25th January 2019) - Mayer, P; Sarter, H; Fumery, M; Savoye, G; Leroyer, A; Dauchet, L; Gower-Rousseau, C; Pariente, B
Abstract: Background: Inflammatory bowel disease unclassified (IBDU) represents 5–15% of new diagnosis of inflammatory bowel disease. However, IBDU is not well defined and high rate of reclassification in Crohn's disease (CD) or Ulcerative colitis (UC) is observed during follow-up. The objective of the present study was to evaluate the evolution of the incidence of IBDU over the period 1988–2014 in a population-based study and its reclassification rate during the follow-up. Methods: All adults (> 17 years old) patients diagnosed with IBDU according to a validated and published algorithm 1 in the French population-based registry EPIMAD from 1988 to 2014, were identified. Follow-up was divided in 3 periods of 9 years (1988–1996, 1997–2005, and 2006–2014). Reclassification was defined as a modification of diagnosis during the follow-up. Results: 24 304 IBD cases (> 17 years) were diagnosed, including 8449 (66.2%) CD, 3839 (30.1%) UC and 476 (3.7%) IBDU. IBDU concerned predominantly males compared with CD and UC population [(51.7% in IBDU population ( n = 246) vs. 45.6% in CD plus UC population ( n = 5602) ( p = 0.009)], with an older age at diagnosis [(36 [26–51] in IBDU population vs. 30 [28–42] in CD plus UC population ( p < 0.001)]. IBDU rate among IBD diagnosis decreased significantly during the study period, from 6% (1988–1996) to 2% (2006–2014) ( p < 0.0001). In the IBDU cohort, 334 (70.2%) only had one diagnosis; 132 (27.7%) had two and 10 (2.1%) had three during follow-up. IBDU reclassification occurred in 108 patients (22.7%). The median time for reclassification was 1 year (IQR [1 −2]) after the diagnosis. Eighty-nine patients (18.7%) were reclassified to CD or UC after a new flare. There was no significant modification of IBDU reclassification rate in CD or UC during the study period 17% (1988–1996) to 21% (2005–2014) ( p = 0.56). Conclusions: In this population-based study, IBDU incidence decreased significantly between 1988 and 2014, probably because of better diagnosis performances allowing CD and UC identification. These results suggest that IBDU may not be a real and significant clinical entity but a misclassification of colonic inflammatory bowel disease. Reference 1. Gower-Rousseau et al. Incidence of inflammatory bowel disease in northern France (1988–1990). Gut 1994.